Determinan Tingkat Pengangguran: Studi Kasus Wilayah Pengembangan Purwomanggung, Jawa Tengah - Natalia Nola Corolina; Jihad Lukis Panjawa (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2020)
This research objective was to analyze the determinants of unemployment rate in PURWOMANGGUNG by using the data panel for Purworejo, Wonosobo, Magelang, Temanggung district, and Magelang city for 2012-2019. Data Resource from Statistics of Central Java province. Analyze method of this research used panel data regression with fixed effect (FE). The result of the study showed that inflation and minim wage have a significant positive impact on the unemployment rate. Others finding demonstrated that economic growth, human development, and minimum wage have no significant effect on the unemployment rate. The study expects that the relevant regional governments of the research hope to find a proper connection between the stability of the inflation value while seeing the magnitude of the effect of the minimum city/regency wages in Purwomanggung on the amount of unemployment. It is expected that the government pays more attention to the calculation of the minimum wage rate currently applied.